Analysis of Trichoderma Application as a Biofertilizer in the Concept of Sustainable Agriculture through Endophytic Microbes - Aidha Zulaika; Darmono Taniwiryono; YS Hidayat; Hery Saputra (Jurnal Rekayasa Lingkungan dan Biosistem, 2023)
Endophytic microbes are microbes capable of colonizing and symbiotic with plant tissues. Trichoderma has been known as an endophytic fungus with a symbiotic relationship of mutualism including root colonization by helping root growth, nutrient absorption and resistance to stress and pathogens. This study consists of two steps, namely: (1) isolation and identification of Trichoderma, (2) endophytic test of Trichoderma isolate by root staining method and plant root culture. Seven isolates were shown to result in better plant growth and plant roots. Based on plant root culture tests, it was found that all plants contained Trichoderma, but based on T. Koningii and T. Polysporum root staining tests. It cannot be certain to colonize the root tissue of test plants. Based on the test results, Trichoderma has the potential to be a biological fertilizer (Biofertilizer) that can help optimal plant growth and can be applied in agriculture that applies the concept of sustainability.